AKTIVITAS ANTIPIRETIK EKSTRAK ETANOL DAUN SAMPARE (Glochidion philippicum (Cav.) C.B.Rob.) PADA MENCIT PUTIH JANTAN (Mus musculus) YANG DIINDUKSI PEPTON - Amala, Ima Choirul; Sarimanah, Jamilah; Wijayanti, Tri (Jurnal Ilmiah Farmasi, 2026)
Background: Sampare leaves (Glochidion philippicum (Cav.) C.B. Rob.) contain secondary metabolites, including flavonoids, tannins, steroids, alkaloids, and saponins, which exhibit antipyretic potential.Objective: This study aimed to evaluate the antipyretic efficacy of the ethanolic extract of sampare leaves in a peptone-induced fever mouse model.Method: The ethanolic extract of sampare leaves was prepared via maceration, and its secondary metabolites were qualitatively identified using standard test-tube reagents. For the in vivo study, twenty-five male Swiss mice (Mus musculus) were randomly divided into five groups. Group I (negative control) received a 0.5% CMC-Na suspension, and Group II (positive control) received paracetamol at a dose of 65 mg/kg body weight (BW). Groups III, IV, and V were administered the ethanolic extract at doses of 200, 400, and 800 mg/kg BW, respectively. Pyrexia was induced via subcutaneous injection of peptone (0.5 mL/g BW). Rectal temperatures were measured using a digital thermometer every 15 minutes for a duration of 180 minutes. Data were analyzed using the Shapiro-Wilk test, followed by repeated measures ANOVA and an appropriate post-hoc test.Results: The maceration process yielded 20.05% (w/w) of ethanolic extract. Phytochemical screening confirmed the presence of tannins, flavonoids, steroids, alkaloids, and saponins. Furthermore, the in vivo evaluation showed that the extract exhibited significant antipyretic activity. The 800 mg/kg BW dose demonstrated the highest antipyretic activity, which was significantly different from the negative control (p < 0.05) and comparable to the positive control (paracetamol). Conclusion: Sampare leaf ethanol extract had antipyretic activity, with an effective dose of 800 mg/kg body weight in mice.